Menyoal Eksistensi Pemerintahan Nagari Di Provinsi Sumatera Barat - Desna Aromatica; Heru Nurasa; Ida Widianingsih; Entang Adhy Muhtar (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2018)
Government Nagari is the leading government in the region of West Sumatra Province, which was held back in 2001. The Government of Nagari has a long history in its implementation. The government that had existed before this independent Indonesia had once been removed as part of the system of state administration and was replaced with a Village Government by Law No. 5 of 1979 concerning Village Government. The enactment of the Law on Regional Government in 1999 became the momentum of the change in the Village Government to be re-established with the Government Nagari in West Sumatra. The hope built on this government is the creation of a government that is in accordance with the characteristics of the communal West Sumatra community. As long as the reorganization of the Nagari Government, it turned out that various institutional problems arose related to its existence as a government institution. Using a qualitative approach, the results of the study show that the hybrid system designed by the Central Government has been the originator of various institutional problems that emerged throughout the administration of the Nagari Government. The birth of Law No. 6 of 2014 concerning Villages, which gave rights to the regions to choose whether to be a Village or Customary Village with other names added to the long list of intricate problems of institutional governance of the Nagari. The Nagari government needs to be a government institution that combines with appropriate indigenous values into the body of public administration through appropriate institutional adaptation.